Tsunami Inundation Modeling and Hazard Mapping Using GIS in Sawarna Beach, Banten Province - Arrisaldi, Thema; Bima, Muhammad Amin Arya; Kanya Kirana Ramadhani Nurapita; Pratiknyo, Puji (Dinamika Teknik Sipil: Majalah Ilmiah Teknik Sipil, 2025)
Tsunamis pose significant hazards to coastal areas, particularly in tectonically active regions like the southern coast of Java. This study models tsunami inundation at Sawarna Beach, Banten Province, using a quantitative spatial analysis approach. By integrating Digital Elevation Model (DEM) data from DEMNAS and land cover data from BIG, a tsunami hazard index is generated through slope analysis, surface roughness coefficients, and cost distance modeling within a GIS framework. The analysis reveals that areas with low surface roughness and gentle slopes are more prone to deep inland tsunami inundation. Vulnerability mapping under simulated tsunami heights (5m, 10m, 15m, and 30m) shows that hazard zones significantly increase with wave height, with the highest exposure at 30m reaching nearly 15 million m². The study underscores the importance of accurate topographic data for disaster mitigation planning and provides essential recommendations for local stakeholders in land use and infrastructure development. These findings serve as a valuable reference for enhancing tsunami preparedness and resilience in coastal communities.